Audit Symposium: 1979/80 Proceedings. (Book Review). - Meyer, Philip E.; Perry, William E. (The Accounting Review, 1981)
Reviews the book "EDP Audit Symposium: 1979/80 Proceedings," edited by Joseph L. Sardinas.